Risk Factors for Ineffectiveness of Posterior Decompression and Dekyphotic Corrective Fusion with Instrumentation for Beak-Type Thoracic Ossification of the Posterior Longitudinal Ligament: A Single Institute Study. Issue 5 (30th March 2017) - Imagama, Shiro; Ando, Kei; Ito, Zenya; Kobayashi, Kazuyoshi; Hida, Tetsuro; Ito, Kenyu; Tsushima, Mikito; Ishikawa, Yoshimoto; Matsumoto, Akiyuki; Morozumi, Masayoshi; Tanaka, Satoshi; Machino, Masaaki; et al.
Abstract: BACKGROUND: Thoracic ossification of the posterior longitudinal ligament (T-OPLL) is treated surgically with instrumented posterior decompression and fusion. However, the factors determining the outcome of this approach and the efficacy of additional resection of T-OPLL are unknown. OBJECTIVE: To identify these factors in a prospective study at a single institution. METHODS: The subjects were 70 consecutive patients with beak-type T-OPLL who underwent posterior decompression and dekyphotic fusion and had an average of 4.8 years of follow-up (minimum of 2 years). Of these patients, 4 (6%; group R) had no improvement or aggravation, were not ambulatory for 3 weeks postoperatively, and required additional T-OPLL resection; while 66 (group N) required no further T-OPLL resection. Clinical records, gait status, intraoperative ultrasonography, intraoperative neurophysiological monitoring (IONM), plain radiography, computed tomography and magnetic resonance imaging findings, and Japanese Orthopaedic Association (JOA) score were compared between the groups. RESULTS: Preoperatively, patients in group R had significantly higher rates of severe motor paralysis, nonambulatory status, positive prone and supine position test, no spinal cord floating in intraoperative ultrasonography, and deterioration of IONM at the end of surgery ( P < .05). In preoperative radiography, the OPLL spinal cord kyphotic angle difference in fused area, OPLL length, and OPLL canal stenosis were significantly higher in group R ( P < .05). At final follow-up, JOA scores improved similarly in both groups. CONCLUSION: Preoperative severe motor paralysis, nonambulatory status, positive prone and supine position test, radiographic spinal cord compression due to beak-type T-OPLL, and intraoperative residual spinal cord compression and deterioration of IONM were associated with ineffectiveness of posterior decompression and fusion with instrumentation. Our 2-stage strategy may be appropriate for beak-type T-OPLL surgery.